2021
DOI: 10.51414/sei2021.029
|View full text |Cite
|
Sign up to set email alerts
|

Barriers and drivers for enterprises to transition to circular economy.

Abstract: This brief provides an overview and discussion of barriers and drivers for enterprises to adopt circular economy practices. The research involved a literature review, an online survey with enterprises in the Southeast Asian region, and an in-person workshop discussing circular practices with private companies and other circular economy stakeholders. Business leaders and enterprises often understand the benefits of circular economy approaches but lack appropriate support from policy and financial institutions t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Table 3 offers an overview of practical contribution made by previous researchers on circularity in eight (8) aspects that are generally considered to be significant in the scientific research. Melati, K et al, 2021 [80] gauged the perception of stakeholders on their own technical knowhow to shift from linear practices to circular practices. Masanet, E.et al, 2020 [70] integrated cloud services into IT Infrastructure which will lead to process improvement.…”
Section: Practical Contributionmentioning
confidence: 99%
“…Table 3 offers an overview of practical contribution made by previous researchers on circularity in eight (8) aspects that are generally considered to be significant in the scientific research. Melati, K et al, 2021 [80] gauged the perception of stakeholders on their own technical knowhow to shift from linear practices to circular practices. Masanet, E.et al, 2020 [70] integrated cloud services into IT Infrastructure which will lead to process improvement.…”
Section: Practical Contributionmentioning
confidence: 99%
“…A salient barrier within this group is the lack of expertise in the circular economy. This includes deep domain knowledge, technical know-how to shift from linear to circular product life cycles-for example, defining a circular business strategy, product design, and material flow-and other relevant insights [45]. As the concept of circularity is still relatively nascent, several works demonstrated that while businesses have a general idea of what it entails, only a handful of them have the necessary knowledge and expertise to appropriately transform their businesses for participation in the circular economy [10,11,15,19,20,24,[39][40][41]43,46,47].…”
Section: Technology Knowledge and Infrastructurementioning
confidence: 99%
“…This leads to the expertise gap between firms gradually widening, despite all parties pursuing the same circularity ambition. Consequently, such behaviors will transpire and affect the establishment of critical ecosystem infrastructures that need to be in place for a smooth transition [45]. These ecosystem infrastructures relate to the product's life cycle, including waste management, treatment facilities, packaging, recycling processes, and more.…”
Section: Technology Knowledge and Infrastructurementioning
confidence: 99%